Avaliar na alfabetização: uma reflexão sobre as dificuldades docentes - Oliveira, Tânia Maria Fernandes de (2006)
Our work leads up to the context of evaluation during alphabetization process as a moment of an educational action cycle that requires planning, teaching and learning of reading and writing. It aimed to research the difficulties lived by teachers of a public elementary school during the specific task of evaluating children in the alphabetization process. This qualitative research took place as a case study at Emília Ramos Municipal School, in Natal, capital city of Rio Grande do Norte State, Brazil. Semi-structured interview and questionnaire were used as fact-gathering proceedings. Two pedagogical advisers and seven teachers formed the group of research subjects. All of them worked with elementary school first cycle classes, in that school, in the year of 2003. The analysis shows that teachers difficulties concern to theoretic questions of conceptual and methodological orders, although these questions indicate an important knowledge of teachers about alphabetization and evaluation. Our reflection about these problems articulates two points: alphabetization and evaluation. Concerning alphabetization, we took reference on Psychogenetic studies of Ferreiro and Teberosky (1985) which emphasizes fundamental points for a coherent evaluation practice: a) objective knowledge is not a beginning data; it is a construction process, which the learner does not conquest step by step on a linear way; b) objective knowledge acquisition happens through a global re-construction, and some of them may seem mistakes if we consider conventional writing but these mistakes are constructive and necessary. We also took reference on Interactionist-constructivist theory. Here, Vygotsky (1984) proposes that writing must be specially understood as language, symbolical activity, cultural practice. So, acquisition of writing process, as language learning, must be understood as a development of abilities relative to symbolical and communicative activity of sense production. On this way, Hoffmann (1994) advises that is necessary to overtake current evaluation practices, limited by their terminality character, only pointing right or wrong questions. According to a new paradigm, valuation appears as one of the mediations by which teachers must indicate re-ordination of pupil s knowledge, and re-organize their own practices too. The comprehensions of these questions plays decisive part in order to overtake our difficulties in evaluating. Besides, it points a way to build a coherent valuate practice, with an emancipating character and able to create new teaching-and-learning situations, leading to a better alphabetization Pedagogy